Egy balkáni periféria megismerése : magyar hadiutazók Albániában - Nagy, Miklós Mihály (Közép-Európai Közlemények, 2011)
Albania was known for the Hungarian society of the turn of the century by the works of Baron Ferenc Nopcsa. Thus it hardly had full picture of the country and its people. The Siege of Shkodër and the First World War changed this picture because lots of Hungarian soldiers fought at the Albanian theater of war. These armed conflicts gave the Hungarian society a better knowledge of Albania. Most of the travel literature about Albania published in Hungary twit with these wars. This paper is a remembrance of Hungarian military travelers and at the same time a first review of them. Also deals with the literary questions, Béla Illés an emblematic figure of the Hungarian socialism who serves in the Albanian front in the First World War wrote his novel “Szkipetárok” (1941) based on his personal memories. The essay deals with the travels of Győző Temesi in detail. He was originally a geographer and as a reserved officer went to the Albanian theater of war voluntarily where he led geographic expeditions. He and Ferenc Nopcsa made the highest contribution to realistically present the geographically closed Albania to the Hungarian society. The paper also counts on natural and geographical dangers the forces of the Austro-Hungarian Monarchy had to surmount during the Albanian campaign. Lack of roads and diseases set back the operations of forces.